THE ROLE AND THE EFFECTS OF NATIONAL SYSTEMS OF INNOVATION IN EUROPEAN REGIONAL GROWTH - George M. KORRES; Aikaterini KOKKINOU; George O. TSOBANOGLOU (European Journal of Geography, 2013)
Research and Development is directly related with industrial infrastructure, productivity effects and regional development, through “national system of innovation” indicating the national technological capabilities, as well as the underlying structure and planning on Research and Development. European technological policy has an important role for the economies of member states. Technological policy aims to reinforce national competitiveness along with convergence between member states. The purpose of this paper is to analyse and examine the evaluation and the development of European Union policy and how it can be implemented to member states. This paper also attempts to examine the effects of innovation activities and the impact of innovation policy on growth, productivity and integration process.